Design and Simulation of 2-Section Wilkinson Power Divider - Talal Altaher Ahmed Mohammed; Ahmed lmhmed Salim Elstia; Abdulghader Basher Morad Jalgum; Ibrahem Mohamed Ibrahem Abdaldaem (Journal of Scientific and Human Dimensions, 2025)
This paper describes the design, simulation, and performance analysis of a two-section Wilkinson power divider with a center frequency of 4 GHz using microstrip line technology. The proposed circuit featuring five 1/4 wavelengths (λ) transmission lines and two isolation resistors provide bandwidth isolation that is superior to a typical single-section’s bandwidth isolation. The entire design flow from synthesis to performance was done using Advanced Design System (ADS) software. Simulation results show that the divider performs well in all critical metrics. The insertion loss per arm is around -3.01 dB, and it provides equal power division among output ports. The input port also shows a good match with a return loss of better than -10 dB and amplified reflected power This design achieves strong output port isolation, enhancing the integrity of the engine operation by minimizing signal interference. Therefore, the obtained results indicate that the divider is an effective and suitable candidate for modern 4 GHz wireless communication systems and RF front ends.
Keywords: Microstrip line; Wilkinson power divider; Quarter-wave; Isolation resistors; Matlab.